AKUNTABILITAS DESA MAJU - Zulaini, Liza; Linda, Linda (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
This research aims to determine the influence of the role of village officials, the internal control system, the organizational commitment of the village government, and the use of the village financial system in Kutaraja District, Banda Aceh City. This type of research is quantitative research. The data used in this research is primary data obtained from distributing questionnaires to village officials in Kutaraja District, Banda Aceh City. The population in this study were all villages in Kutaraja District. Respondents in this study totaled 78 people. The sampling technique uses a census sample.The data in this study are from villages in Kuta Raja District, Banda Aceh because in Kutaraja District, only 33.3% of villages have IDM status as Independent Villages, the rest are still Developed Villages. The data analysis method used is multiple linear regression analysis using the SPSS version 25 application. The results of this research show that the role of village officials, the internal control system, the organizational commitment of the village government, and the use of Siskeudes simultaneously influence the accountability of village fund management. The results of this research also show that the role of village officials, the internal control system, and the use of Siskeudes have a positive effect on the accountability of village fund management, while the organizational commitment of the village government does not affect the accountability of village fund management in Kutaraja District, Banda Aceh City.